Technological Advancements in Humanitarian Aid - Zarei, Hossein; Baharmand, Hossein; Bashiri, Mahdi; Madanian, Samaneh (Elsevier BV, 2024)
[From Introduction] In the rapidly evolving landscape of humanitarian aid, technological advancements have created new possibilities to improve the efficiency, effectiveness, and sustainability of humanitarian operations. However, the humanitarian sector is associated with slow technology adoption rates and poor information and communication technology infrastructure [1]. This necessitates exploring how technology can be contextually embedded and how the sector's peculiarities can be addressed to achieve “technological advancements in humanitarian aid.” This is the purpose of this special issue.
Keywords: 4404 Development Studies; 4406 Human Geography; 44 Human Society; 0502 Environmental Science and Management; 1117 Public Health and Health Services; 1604 Human Geography; 4404 Development studies; 4406 Human geography